Vaccine Hesitancy, Vaccine Acceptance, and Recommendations about the COVID-19 Vaccines - Alexander, Cheryl Ann; Wang, Lidong; Shah, Vijay (Jour Med Resh and Health Sci, 2021)
This paper presents COVID-19 vaccines, the types of vaccine manufacturing, and SARS-CoV-2 variants and likely resistance to COVID-19 vaccines. Since the vaccines were distributed and entered the healthcare market for the general population, people have either readily accepted the vaccine or they have developed hesitancy—a term coined after the vaccines entered the healthcare market for the general population. Vaccine hesitancy refers to the uncertainty some people have about various aspects of vaccination, whether it is the manufacturing process of the drug, the personal impact of the political climate (e.g., vaccine mandates, political opinions during speeches and interviews, etc.) surrounding the vaccine, or the impact of social media (e.g., Facebook and Twitter misinformation algorithm, etc.) or the impact from media coverage, which has been less than ideal (e.g., distortion of COVID-19 facts and figures, dishonesty about the vaccine itself, promotion of one political party’s agenda, misinformation related to variants, etc.) These distorted views have impacted the general public far much more than practitioners have and vaccination rates have fallen amid the chaos of the pandemic itself, the aforementioned factors, and the reduction of efficacy among vaccinated individuals leading to higher COVID-19 cases, hospitalizations, and deaths and a disparity among minorities as they are the hardest hit by COVID-19 and they have the highest rate of unvaccinated individuals, potentially related to the suspicions put in the minds of the US public by politicians during the 2020 election cycle. Public opinion has also lagged due to the rates of infection now showing in the vaccinated. Disparities still exist in vaccine administration, whether from a lack of education about the vaccine’s effects, development, etc. and suspicions about the vaccines because the government seems to be forcing individuals to take the vaccines whether they have a valid reason for putting off the vaccine or not. Blockchain can be use in disparate vaccine administration and to promote cybersecurity of data and other private information in a vaccine chain. Recommendations for vaccination in pregnant women and breastfeeding is also discussed. Other significant issues such as the duration of vaccine protection, to get a booster or not, and blending vaccines.